Perkembangan Moral Anak Awal Dan Anak Akhir - Syafira Sahara Saleh; Nurdina Hasanah; Azizah Febryani Nasution; Dayang Lidya Fitriah; Sri Wahyuni (Universitas Maritim AMNI Semarang, 2024)
The moral development of children in the early and late stages of their lives is a crucial process in shaping their character. In the early stage, children tend to rely on the influence of adults, such as parents and teachers, to understand the concepts of right and wrong. They often strictly follow rules and avoid moral violations. In contrast, in the later stage, the moral development of children becomes more complex. They start to develop a deeper understanding of morality based on the values and principles they have learned throughout their lives. Children in this stage can consider the moral consequences of their actions and develop autonomy in making moral decisions. A better understanding of the moral development of children can help adults, such as parents and educators, support the healthy moral development of their children throughout the early and late stages of their lives. Set a good example: Children tend to imitate the behavior of adults around them. Therefore, it is important for parents and adults around children to set good examples in behavior, attitudes and communication. Teach moral values: Teach children about moral values ​​such as honesty, responsibility, empathy, mutual help, patience, etc. Discuss these values ​​with them and provide concrete examples of how these values ​​are applied in everyday life.